Talking about Race in Cuba: Four Trans-Atlantic African Diaspora Women Share Their Experience. (1st December 2015) - Nataka Moore; Tiffany McDowell; Mildred Watson; Caridad Morales Nussa
Abstract : Descendants of the African Diaspora have encountered different challenges to well-being within their respective countries. In Cuba, it appears that while the Cuban Revolution attempted to level the outcomes for all citizens, Black Cubans remain marginalised and targets of discrimination. We, three African American and one Black Cuban women researchers, used a roundtable approach to analyse our experiences in Cuba. Using our individual reflections as data, the four of us sought to make meaning of cultural identity and expression within Cuba, and impact on well-being. Implications of this work can inform interventions for well-being of multiple African Diasporic populations in North and South America.